Dynamics analysis of 3 axis gantry type multipurpose CNC machine - Goh, Ming Hui (2013)
The determination of the natural frequency and the resonance is important before the machine can be use. If the natural frequency is occur and the resonance will be occur also and it will make the damage to the machine when the machine is using. From this paper, modal analysis is used to determine the natural frequency. Modal analysis is a process whereby describe a structure in terms of its natural characteristics which are the frequency, damping and mode shape of its dynamic properties. From the experiment that was carrying out, the natural frequency is occur at 24Hz. From the result, when the machine is running with the speed of 50Hz or 100Hz, it doesn’t meet with the natural frequency which is 24Hz. From the experiment that was carrying out, it was shows that the machine can be use as user to milling process. Most machines produce low levels of vibration when designed properly. During operation, all machines are subjected to fatigue, wear, deformation, and foundation settlement. These effect cause an increase in the clearances between mating part, misalignments in shafts, initiation of cracks in parts, and unbalances in rotors. All leading to an increase in the level of vibration, which cause additional dynamic loads on bearings. As time progresses, the vibration level continue to increase, leading ultimately to the failure or breakdown of the machine. So, the maintenance is needed for all the time the machine is use.